Some evidence on the impact of internal audit on external audit fees: Data provided by the Institute of Internal Auditors are subject to restrictions - Hazami‐Ammar, Sourour (The Journal of corporate accounting & finance, 2019)
We examine responses of 2,160 internal auditors to a global survey of the internal auditing profession carried out by the Institute of Internal Auditors Research Foundation from 2009 to 2013. We found that when the internal audit function's (IAF's) quality is high, the external audit fees will be low. This result confirms the substitution effect. We also found that when internal audit hours work increase, audit fees will be high; indicating a complementary effect between these variables. The internal auditor can be the external audit assistant and fully engaged in specific monitoring and control tasks. Nevertheless, he also may be an independent partner of an external audit and fully engaged in corporate governance. If the external auditor apprehends that audit risk is low due to the quality of the IAF, he will require lower fees. If the IAF's work devoted to external audit is high, a signal of a great firm commitment in reinforcing corporate governance is transmitted. Such signal proves the company's willingness to invest more in improving the external audit quality and fees will be high.